Mid-atlantic freshwater wetlands: advances in wetlands science, management, policy, and practice - Wardrop, Denice Heller; Brooks, Robert P. (Springer New York, 2013)
Mid-Atlantic Freshwater Wetlands: Advances in Wetlands Science, Management, Policy, and Practice summarizes over two decades of work by Riparia, a Center at The Pennsylvania State University. This comprehensive book delves into the ecology and conservation of these critically important and valued ecosystems. The 14 chapters written or edited by Riparia's leadership and colleagues, focus on understanding the ecology of freshwater wetlands and the stressors that affect them in a watershed context. Wetlands are viewed not as isolated patches, but as part of an integrated aquatic and terrestrial system. Early chapters address concepts of reference and hydrogeomorphic classification. The current state of our knowledge about hydrology, hydric soils, plants, and wildlife is covered in the middle chapters. Later chapters include policy issues and practice, with emphases on monitoring and assessment, restoration and mitigation, and conservation and regulatory programs. There are extensive reviews and listings of recent literature, and linkages to Riparia's website where supplemental information can be found.